RESPON IRELAND PALESTINE SOLIDARITY CAMPAIGN (IPSC) TERHADAP KEBIJAKAN RUU LARANGAN IMPOR PRODUK ISRAEL TAHUN 2018 - Fiani Nurmalasari (: 2621-0924)
This study examines how the response of the Ireland Palestine Solidarity Campaign (IPSC) to Irish foreign policy, namely the Bill on the Prohibition of Importing Israeli Products in 2018. This research aims to understand how the significance of the role of transnational networks carried out by IPSC in the perspective of International Relations studies in terms of the framework Thoughts of CSOs and the Transnational Advocacy Network (TAN) especially leverage politics and accountability politics. This study applies a qualitative approach with descriptive analysis techniques sourced from primary data and secondary data. The results show that horizontally, IPSC as a CSO has a positive impact on the creation of awareness of the Irish public to support the Palestinian cause. As for vertically, the IPSC response has become significant in advocating for various transnational network actors, especially in influencing the legal level of the Irish Government to pass the legal products of the Prohibition of Importing Israeli Products Bill 2018. In the realm of international relations, civil society has a significant role in changing levels. International politics. This shows that currently international actors are not only countries but also the international community, both individually and in organizations, having a big share in the process of making a country's foreign policy.Keywords: IPSC, Israeli Products Import Prohibition Bill Policy, Civil Society Organization, Transnational Advocacy Network (TAN), Boycott, Divestment and Sanctions (BDS).